2022
DOI: 10.1111/jpc.16052
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy and adenoidectomy in children: The impact of timing of surgery and post‐operative outcomes

Abstract: Aim: To investigate the impact of adenotonsillectomy (ADT) and adenoidectomy (AD) on child health and evaluated their post-operative complications. Methods: We included all children aged <16 years undergoing ADT (tonsillectomy AE adenoidectomy) or AD in New South Wales, Australia, 2008-2017. Health information was obtained from administrative hospitalisation data. Rates of post-operative complications and reoperation were evaluated using generalised estimating equations and Kaplan-Meier methods, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Other countries such as Scotland and Australia have reported an increase in the rates of adenotonsillectomy and adenoidectomy among younger children. One main cause of the rise in adenotonsillectomy has been identified as the increased number of young children identified and treated for OSA or other less severe respiratory problems (Schneuer et al, 2022). Based on this study, it was found that 4 out of 7 patients (57.1%) with adenoid hypertrophy and 21 out of 31 patients (67.7%) with adenotonsillar hypertrophy experienced OSA.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Other countries such as Scotland and Australia have reported an increase in the rates of adenotonsillectomy and adenoidectomy among younger children. One main cause of the rise in adenotonsillectomy has been identified as the increased number of young children identified and treated for OSA or other less severe respiratory problems (Schneuer et al, 2022). Based on this study, it was found that 4 out of 7 patients (57.1%) with adenoid hypertrophy and 21 out of 31 patients (67.7%) with adenotonsillar hypertrophy experienced OSA.…”
Section: Discussionmentioning
confidence: 80%
“…Respiratory disturbances encompass various conditions ranging from snoring to the most severe form of OSA. Obstructive sleep apnea or OSA is characterized by irregular breathing and sleep patterns that can be observed during nighttime polysomnography (Schneuer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the year 2010, a US study reported the adenotonsillectomy rate as 0.68%, whereas this rate was indicated to be 1.2% in a 2016 Swedish study [ 32 ]. In another study, based on data from 2017, the adenotonsillectomy prevalence was reported as 0.70% [ 33 ]. In this study, 20.3% of all patients were diagnosed with adenoid and/or tonsil hypertrophy, a similar percentage to the study reporting an adenoid hypertrophy rate of 19.8% and a tonsil hypertrophy rate of 16.2% in patients with SDB [ 23 ].…”
Section: Discussionmentioning
confidence: 99%